Breaking down apoptosis: animating programmed cell death in 3D for a pathology curriculum. (2nd October 2018) - Thouvenot-Nitzan, Elvire; Oparka, Richard; Campbell, Annie; Erolin, Caroline
Abstract: Contemporary medical education is expected to keep up with the rapidly expanding corpus of medical scientific knowledge to train informed doctors. Swift communication and assimilation of complex concepts are required, yet traditional teaching methods are often suboptimal means to this end. This paper details the making of a concise 3D animation on the apoptotic pathways, designed to improve first-year undergraduate medical students' grasp of cell signalling. A simplified visual language was adopted to increase the effectiveness and expedite the production of beginner molecular biology animations. Favourable student feedback suggests that the chosen design approach could yield further positive results.